An Intertextual Approach to the Political Poetry of Griselda Alvarez - Margarito Gaspar, Mayra; Quezada Camberos , Silvia Magdalena (Integrated Journal for Research in Arts and Humanities, 2023)
The political poetry of Griselda Álvarez has played a fundamental role in the history of Mexico by highlighting silenced voices and social struggles through her verses. As the first female governor in Mexico, Álvarez paved the way for women in politics, and her poetry reflects her commitment to social justice and women's rights. Her poems, including Canto a las barbas, address pressing issues such as gender inequality, political oppression, and the fight for freedom, offering a critical and poetic perspective on the political reality of her time. Griselda Álvarez's work reveals the complex nature of art, which allows for connections between the ineffable essence of being and historical social issues. In this study, we use an intertextual analysis to approach her literary creation from a critical perspective, through which we observe that poetry constructs feelings, sensations, and beauty, while also serving as a tool for resistance and denunciation.